Constructing citizen engagement in health research priority‐setting to attend to dynamics of power and difference. Issue 1 (25th June 2018) - Pratt, Bridget
Abstract: Engaging citizens is vital to achieving people‐centred health research. This paper aims to put attention to dynamics of power and dynamics of difference back at the centre of citizen engagement in health research priority‐setting. Without attention to power and difference, engagement can lead to presence without voice and voice without influence, particularly for disadvantaged and marginalised groups. By analysing six key bodies of literature, the paper first identifies the different components of engagement—who initiates, for what purpose, who participates, and how they participate—and the dynamics of power and dynamics of difference relevant to them. For each component of engagement, the ethical considerations relating to those dimensions of power and dimensions of difference are characterised for the research priority‐setting context and preliminary guidance on how they might be addressed is provided. An initial framework comprised of a series of questions reflecting these ethical considerations has been developed for use by researchers and citizens when designing engagement processes for research projects. Where researchers and citizens attend to the framework's questions and then revise their priority‐setting processes' design to better represent diversity and mitigate power disparities, more inclusive citizen engagement is promoted. Disadvantaged and marginalised groups are more likely to be present and heard, which, in turn, will help generate research projects with topics and questions that encompass and more accurately reflect their health needs.